Computer animation as a tool to visualize effects of seismic wave propagation inside heterogeneous media - P. Lanucara; A. Caserta (Annals of Geophysics, 2000)
A technique to make computer animations representing the propagation of antiplane shear waves in heterogeneous dissipative media is presented. The aim is to develop a useful tool to better investigate the physics of site effectsin the 2D approximation. We apply this technique to real case studies that were the subject of previous papers. For each case study a movie has been made to illustrate the wavefield time evolution and its interaction with the geological structure. All the movies can be seen and downloaded at the web site http://sigfrido.ingrm.it/movies.html. The paper shows the most representative frames of movies, providing an overview of the role played by the topographic irregularities and the geometry of internal discontinuities in trapping and focusing energy. The details of the dynamics are well visualized through movies. Particular attention is devoted to the representation of simulated ground motion in sediment-filled basins under resonance conditions. Problems related to color scales and frame normalization are analysed and discussed.